ASSESSMENT OF DYNAMIC GROWTH OF FOOD PRODUCTION IN BULGARIA - Kopeva, Diana; Blagoev, Dimitar; Sterev, Nikolay; Zhelev, Paskal (Acta Scientiarum Polonorum. Oeconomia, 2015)
Perspectives for competitive growth are put in the core of the re-industrialization policy of the European Union for the next program period, and respectively are key issue for the Bulgarian industrial policy. Re-industrialization of the Bulgarian economy is possible in terms of support for competitive industries at present, but also to support industries that are at the bottom of competitiveness. The methodology for selection of appropriate "priority" sub-sectors and production specializations, is based on the following two principles: 1. A combination of economic criteria (at national and company level) and social criteria; 2. Measures targeted both: certain sub-sectors and production specializations that either have a competitive advantage, or are at the bottom of the rankings for competitive advantage. On the basis of analysis six production specializations in food industry were identified for which specific policy measures have to be developed along the chain raw materials/inputs - production-marketing/export.